Hadiths on the Dead and Societal Consumption Ethics: A Musykil al-Hadith Study from the Perspective of Islamic Law - Zarkoni; Munafaroh (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
Understanding the mayit hadith has significant implications for ethical consumption behavior in Muslim communities. This study aims to analyze how the interpretation of the mayit hadith shapes consumption ethics and social consumptive practices through the Musilil Hadith approach. A qualitative case study methodology was employed, using in-depth interviews, participatory observation, and literature documentation to collect data from lecturers, pesantren teachers, and social practitioners experienced in managing consumption related to death. Findings indicate that understanding the mayit hadith serves as a moral filter, guiding expenditure management, wise need selection, and the avoidance of waste. Scientific analysis of the sanad and matan emphasizes practical guidelines for prudent consumption. This research contributes a novel integration of textual hadith study with social consumption practices, offering ethical guidance grounded in religion. Practical implications include education, counseling, and modules for responsible consumption management.